2011
DOI: 10.3758/s13421-011-0096-x
|View full text |Cite
|
Sign up to set email alerts
|

When story characters communicate: readers’ representations of characters’ linguistic exchanges

Abstract: Klin, Ralano, and Weingartner (2007) found transfer effects when a phrase, described as part of a note one character had left for another, was repeated across two passages. However, when the phrase was part of a note in story A and part of a conversation in story B, transfer effects were eliminated (Klin & Drumm, 2010). Klin and Drumm concluded that readers encoded the perceptual features of story characters' linguistic exchanges and that the mismatch (visual vs. auditory) eliminated transfer effects. The pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
(97 reference statements)
0
6
0
Order By: Relevance
“…The current work goes a step further by examining the influence of the match between the character's and the reader's actions. It is possible that the readers in Drumm and Klin (2011) encoded the information about the critical phrase being either written or spoken by using a symbolic, or linguistic, representation. However, even if it can be argued that a representation that is symbolic is grounded in the physical world of the comprehender (Sanford, 2008), it is difficult to explain the effect of the match between the participant's and the character's actions without arguing that readers form some type of sensorimotor simulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current work goes a step further by examining the influence of the match between the character's and the reader's actions. It is possible that the readers in Drumm and Klin (2011) encoded the information about the critical phrase being either written or spoken by using a symbolic, or linguistic, representation. However, even if it can be argued that a representation that is symbolic is grounded in the physical world of the comprehender (Sanford, 2008), it is difficult to explain the effect of the match between the participant's and the character's actions without arguing that readers form some type of sensorimotor simulation.…”
Section: Discussionmentioning
confidence: 99%
“…Just as readers mentally simulate the perceptual details involved in a character’s movements (e.g., Glenberg & Kaschak, 2002), we asked whether readers also simulate the perceptual details involved in a character’s linguistic actions. We know from previous studies (Drumm & Klin, 2011; Klin & Drumm, 2010; Klin, Ralano, & Weingartner, 2007) that readers can encode and utilize quite detailed information about characters’ linguistic exchanges. Although these studies did not manipulate the action of participants, as was done in the current work, it is interesting to note the level of detail that was encoded about the story characters’ linguistic actions.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies by Klin and Drumm (2010; Drumm & Klin, 2011) showed that readers mentally represent the modality in which information is presented to a story character. They found that when an identical utterance is presented to a character within modalities (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence for this phenomenon, called auditory perceptual simulation (APS), is both behavioural and neurological. As far back as 1977, Kosslyn and Matt reported that the prose of a purported "slow speaker" was likely to be read more slowly than the prose of a purported "fast speaker", a result that has since been replicated in several ways (e.g., Alexander & Nygaard, 2008;Drumm & Klin, 2011). Also, specific speakers' voices are simulated under certain conditions during silent reading (Filik & Barber, 2011;Kurby, Magliano, & Rapp, 2009).…”
mentioning
confidence: 99%